Effects of Storage Temperature and Duration on Bioactive Concentrations in the Seed and Oil of Brassica napus (Canola). Issue 2 (24th October 2017) - Flakelar, Clare L.; Doran, Gregory S.; Howitt, Julia A.; Luckett, David J.; Prenzler, Paul D.
Abstract : The effects of storage temperature and duration on phytosterol, tocopherol and carotenoid concentrations are assessed in canola seed, and oil extracted using two different techniques, over a 10 month period. Increases to oxidation indices ( K 232, K 270 and Δ K ) are observed in the solvent extracted oils, and in the seed stored at 40 °C, indicating the formation of primary and secondary oxidation products. Only small decreases in the concentrations of γ‐tocopherol and β‐carotene are observed across the 10 month period. Phytosterol concentration decreases over time, with similar degradation rates observed in both seed and oils. α‐tocopherol and lutein are well preserved up to 7 months in all samples, despite oil oxidation, and further research will be needed to identify the cause for retention of bioactives. The results indicate that in order to preserve phytosterols, tocopherols and carotenoids in seed stored in bulk for extended periods, storage temperatures should remain at or below 21 °C. Moreover, oil stored at 4 °C or −18 °C, results in high bioactive concentrations and slows the onset of oil oxidation, compared to oil stored at room temperature. Practical Applications : Industrial storage conditions have been shown to greatly influence the chemical processes that occur with canola seed and oil. However, the effects of typical storage conditions on phytosterols, tocopherols and carotenoids in canola seed and extracted oil, are not yet known. This study presents the effects of typical seed and oil storage conditions on phytosterol, tocopherol and carotenoid concentrations, whilst monitoring oxidation indices and FFA, and thus provides information to seed handlers and oil processors on storage conditions that may preserve these bioactives. Moreover, the different behaviours of bioactives are examined relative to the oil extraction technique used, and present opportunities to optimise oil extraction techniques. Time series plots for α‐tocopherol concentrations in canola oil stored at different temperatures over 280 days, illustrating a difference in behaviour between the solvent extracted oil and the hand‐press extracted oil. Abstract : Time series plots for α‐tocopherol concentrations in canola oil stored at different temperatures over 280 days, illustrating a difference in behaviour between the solvent extracted oil and the hand‐press extracted oil.